'Our Dear Reşadiye': The Legend and the Loans behind Ottoman Naval Rearmament, 1908–1914. Issue 2 (4th March 2022) - Conlin, Jonathan
Abstract: The seizure of the newly-built Ottoman dreadnought Reşadiye by First Lord of the Admiralty Winston Churchill on 31 July 1914 is widely held to have spurred the Young Turk regime in Istanbul to contract an alliance with Germany and enter the Great War at its side. This owing to widespread belief (still held by historians today) that it and a second seized dreadnought had been fully paid for by donations to the Ottoman Navy League collected from across the Ottoman Empire and beyond. Drawing on the archives of banks and of Vickers, who constructed the Reşadiye, this article demonstrates that the warships were in fact paid for by funds lent by British, French and German banks—as well as by Vickers itself. Drawing on Ottoman newspapers of the time, it explains how the Navy League myth developed, constraining Ottoman room for manoeuvre in the crucial months of summer 1914.